Differences in complete denture longevity and replacement in public and private dental services: A propensity score-matched analysis of subsidised dentures in adult Australians across 20 years - Taylor Marietta; Masood Mohd; Mnatzaganian George (WILEY, 2022)
Objectives: To examine the differences in treatment outcomes for patients who received subsidized complete dentures in private dental clinics and in public dental clinics over 20 years in Victoria, Australia.
Methods: Between 2000 and 2019, 187 227 complete dentures were provided to eligible public patients by the Victorian public dental system. Of these, approximately 52% were provided to public patients in private clinics through the voucher system. Of the 97 107 participants who received denture care in private clinics, 70 818 were matched 1:1 by propensity score (PS) quantiles with participants who received denture care in public clinics. The PS matching balanced the characteristics between these two groups. Subsequently, a conditional logistic regression model investigated the binary outcome of denture replacement whilst a conditional Poisson regression modelled the number of years to denture replacement. A frailty Cox regression after PS matching investigated denture survival over time.
Results: Dentures provided in public clinics had a mean time to replacement of 5.5 years (SD: 34.0) and 25.9% were replaced during the observation period. In the first year of denture service, incidence rate per person year (IR) for complete denture replacement in public clinics was 0.04 (95% CI: 0.04-0.04). Dentures provided in private clinics had a mean time to replacement of 6.5 years (SD: 3.8) with 29.4% replaced during the observation period. In the first year of denture service, the IR for complete denture replacement in private clinics was 0.02 (95% CI: 0.02-0.02), which was less than half that of the public IR. Multivariate analyses found that although private dentures were more likely to be replaced during the observation period than those provided in the public sector (odds ratio [OR]: 1.31, 95% CI: 1.28-1.35, p < .001), they had greater longevity (incidence rate ratio [IRR]: 1.23, 95% CI: 1.23-1.24, p < .001). Longer longevity of private dentures was also supported by the frailty Cox regression showing that private dentures had a reduced hazard of denture replacement over time (better survival) in comparison to public dentures (hazard ratio [HR]: 0.94, 95% CI: 0.92-0.97, p < .001). Probabilistic sensitivity analysis supported the study findings.
Conclusions: Increased denture longevity, higher rates of denture replacement and lower rates of early denture replacement were associated with receiving denture care in private clinics as compared with dentures provided in the public sector.